2013
DOI: 10.1177/105268461302300103
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Analysis of the Longitudinal Impact of Principal Change on Elementary School Achievement

Abstract: Recent reform initiatives, such as the Title I School Improvement Grants and Race to the Top, recommended a principal change to jump-start school turnaround. Yet, few educational researchers have examined principal change as way to improve schools in a state of systematic reform; furthermore, no large-scale quantitative study has determined the immediate or longitudinal impact of principal change on school performance. Using 9 years of school performance data, this study examined the impact of principal change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…Table 8 summarizes the findings from the one tier III study: Changing principals does not correspond to achievement gains. This is consistent with findings from the broader literature relating principal turnover to student achievement, which finds either no relationship or a negative relationship between turnover and outcomes (Hochbein and Cunningham, 2013;Béteille, Kalogrides, and Loeb, 2012;Miller, 2013). Based on this review, principal replacement would not be considered evidence-based according to ESSA at this time.…”
Section: Strategic Staff Managementsupporting
confidence: 77%
“…Table 8 summarizes the findings from the one tier III study: Changing principals does not correspond to achievement gains. This is consistent with findings from the broader literature relating principal turnover to student achievement, which finds either no relationship or a negative relationship between turnover and outcomes (Hochbein and Cunningham, 2013;Béteille, Kalogrides, and Loeb, 2012;Miller, 2013). Based on this review, principal replacement would not be considered evidence-based according to ESSA at this time.…”
Section: Strategic Staff Managementsupporting
confidence: 77%
“…The retention of school administrators is desirable only when the departing principal is an effective one, and consequently, such departure results in an undesirable education outcome for the school and its community. In contrast, some principals should be destabilized mainly where there is sense of urgency for change, and if the infusion of new perspectives and ideas is desired, and where there is organizational inertia and stultification, particularly in underperforming school contexts (Hochbein & Cunningham, 2013). Such change may facilitate new vision and direction in the school, and help override change resistance, as well as staff investment in previous norms (Jas & Skelcher, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Despite some unclear findings about how principals influence student achievement or school performance (e.g. Hattie, 2009;Hochbein & Cunningham, 2013), many more studies have shown that principals have an important effect on student achievement (Boberg & Bourgeois, 2016;Chiang et al, 2016;Cotton, 2003;Dempster, 2001;Grissom et al, 2015;Hallinger & Heck, 1998;Hattie, 2015;McCullough et al, 2016;Pelfrey, 2006;Stronge et al, 2008;Tan, 2018). One intermediary explanation for this relationship may be that principals influence teachers; this is valid since many studies have confirmed that principals' instructional leadership affects teacher practices (Lambersky, 2016;Mangin, 2007;Proffitt-White, 2017;Quinn, 2002;Rigby et al, 2017;Supovitz et al, 2010).…”
Section: Principals and Mathematics Reformmentioning
confidence: 99%